Komunikasi Kelompok dalam Melestarikan Budaya Betawi di Sanggar Setia Warga - Rina Astriani (Asosiasi Dosen Muda Indonesia, 2025)
The purpose of this research is to see how group communication strategies in preserving Betawi culture as a cultural heritage in Sanggar Setia Warga. The theory used in this research is the theory of diffusion of innovation. The research method used is descriptive qualitative with data analysis techniques using observation, interviews, documentation, and literature study. The results of this study indicate that the communication strategy that can be carried out in preserving betawi culture through this Diffusion of Innovation Theory is how innovations, ideas, or cultures are spread in society. In this context, the first component is innovation, which in this theory refers to new approaches applied by Sanggar Setia Warga, such as the use of digital media to disseminate Betawi cultural content. The second component is communication channels, where Sanggar Setia Warga utilizes various channels, both mass media such as television and radio, as well as digital platforms such as social media to reach a wider audience. The third component is the time period in the diffusion of innovation, which is seen in the process of adopting Betawi culture not instantly, but takes a long time to be accepted by the community. And the last component is the social system, which includes collaboration between Sanggar Setia Warga and various stakeholders, such as the government and local communities. Through this strategy, Sanggar Setia Warga has managed to maintain the sustainability of Betawi culture in the modern era.